2016
DOI: 10.1097/md.0000000000002873
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Carcinomas in Young (Younger than 40 Years) Chinese Patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 46 publications
4
32
2
2
Order By: Relevance
“…A small number of larger analyses have been conducted but have limited or no data from the last 10 years [4,10,34]. Several findings regarding patient presentation in this hospital-based analysis are consistent with past reports, including higher rates of female sex, non-white race, signetring or diffuse histology, advanced clinical stage disease, higher grade, advanced T-stage, and nodal involvement [4][5][6][7][8][9][10][11][12][13]. Among young adult patients, findings that have not been previously reported including a larger proportion of patients treated in metropolitan areas, in the northeast, at facilities in the top decile of gastric cancer patient volume, and with private, Medicaid, or no insurance and higher frequency of bone metastases.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A small number of larger analyses have been conducted but have limited or no data from the last 10 years [4,10,34]. Several findings regarding patient presentation in this hospital-based analysis are consistent with past reports, including higher rates of female sex, non-white race, signetring or diffuse histology, advanced clinical stage disease, higher grade, advanced T-stage, and nodal involvement [4][5][6][7][8][9][10][11][12][13]. Among young adult patients, findings that have not been previously reported including a larger proportion of patients treated in metropolitan areas, in the northeast, at facilities in the top decile of gastric cancer patient volume, and with private, Medicaid, or no insurance and higher frequency of bone metastases.…”
Section: Discussionsupporting
confidence: 81%
“…Though young adults are less commonly affected by gastric cancer, there have been mixed reports about the prognosis of younger patients from studies around the world. Some have suggested that young patients more often have diffuse-type and signet-ring histologies, higher stage disease, more frequent nodal involvement, and higher postoperative mortality [4][5][6][7][8][9][10][11]; and others have explored the idea of gastric cancer in the young as a different clinical entity, raising questions for the role of differential management [12,13]. Most studies are reports from single institutions or use the Surveillance, Epidemiology, and End Results (SEER) database, which lacks detailed treatment data unless combined with data from the Medicare-linked database.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of young age varies among studies, but most research would define it as being younger than 40 years of age. [ 7 , 8 ] Reports have shown an increasing trend of GC in younger patients, [ 9 , 10 ] and the clinicopathological features in this group of patients showed more diffuse lesions and advanced tumor stage compared with older GC counterparts, although whether this translates into worse prognosis in this group remains controversial. [ 11 , 12 ]…”
Section: Introductionmentioning
confidence: 98%
“…The high diversity and plasticity of gastric epithelial stem cells is responsible for 2 major groups of EGC: proximal cardiac carcinoma and distal noncardiac carcinoma with different epidemiology, pathology, clinical presentation, and prognosis [10]. On the other hand, the hereditary form of early-onset gastric carcinoma is associated with dysregulated gastric stem cells, which occur mainly in the corpus-fundic regions through the CDH-1 gene mutation-related and -unrelated unknown mechanisms [11,12]. …”
Section: Heterogeneity Of Gastric Epithelial and Stem Cellsmentioning
confidence: 99%
“…the lesser curvature side of the antrum-angularis in patients in 60 years and the cardia for male patients over 40 years. For young women with the family history and clinical suspicion for gastric carcinoma, the corpus and fundus, especially, near the greater curvature, are the most vulnerable regions for early-onset carcinoma [11,12,13]. …”
Section: Gastric Regions At High Risk For Early Carcinomamentioning
confidence: 99%